Novel Group Acceptance Sampling Plan for Modified Power Exponential Distribution with Application to Quality and Reliability Analysis (Contemporary Mathematics, 2025)
This study introduces a group acceptance sampling plan (GASP) utilizing a truncated life test in which the lifespan of an object follows a modified power exponential distribution. The median is used as a quality measure for various constraint design criteria, including consumer and producer risks, as well as the minimum group size required for a specified acceptance number and test termination time. The optimized values are presented in tables and graphs. In addition, we illustrate our findings using real-world datasets. Furthermore, we compared different distributions under the GASP framework and compared GASP with the ordinary sampling plan (OSP) approach. Simulations were performed using the estimated parametric values. Future research is recommended to further enhance the efficiency and quality control procedures.
Keywords: producer risk; optimized values; quality index; sampling plan; GASP